Perancangan Alat Simulasi SILO VISCOSE Otomatis Berbasis Kendali Elektro Pneumatik - Muhammad Yugi Wibowo; Sandy Bhawana Mulia (Jurnal Teknologi dan Rekayasa Manufaktur, 2019)
The vicose silo simulation tool is a production process that is intended to drain the pulp, and the production process uses pneumatic control as a rescue and direct human work. In this paper a control system is designed for a viscose silo simulation tool with a close loop system. Control system equipment that is designed using a water level float sensor component or commonly referred to as a water level float sensor. The float sensor water level is used to detect the full level of the silo which then gives a signal directly to the PLC and will then be processed and output will be output to the solenoid valve to move the cylinder used to open and close the slide gate on the silo channel. The method used in making this tool is construction design, electro pneumatic system planning, and assembly. Based on testing that has been done, the system can work well and in accordance with the design.